Fine Structure of the Configurations 3d, 3d4s5s, 3d5s, 3d4s4d and 3d5s of Neutral Scandium Atom - Öztürk, İpek K. (İstanbul Kültür Üniversitesi Yayınları, 2004)
lnvestigation of parametric analysis of the fine structure (fs) for the even parity configurations 3d3. 3d4s5s.3d5s2,3d4s4d end 3d25s configurations of atomic Scandium (Sc I) was aimed in this work. Fine structure calculation has been done by using multi configuration fit method. More precise values for the theoretical g foctors are also reported .

Bu çalışmada, Skandiyum I (Sc I) elementinin çift pariteli 3d, 3d4s5s, 3d5s, 3d4s4d ve 3d25s konfigürasyonlarının ince yapısının parametrik analizinin incelenmesi amaçlandı. İnce yapı hesapları çok-konfigürasyonlu fit metodu kullanılarak yapıldı. Aynı zamanda hassas olarak belirlenen teorik g faktörleri verildi.
Keywords: fine structure parameters; g-factor; scandium; skandiyum; g-faktörü; ince yapı parametreleri